2014
DOI: 10.1080/10408398.2012.654863
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Properties of Wheat Gliadins: A Review

Abstract: Gliadins account for 40-50% of the total storage proteins of wheat and are classified into four subcategories, α-, β-, γ-, and ω-gliadins. They have also been classified as ω5-, ω1, 2-, α/β-, and γ-gliadins on the basis of their primary structure and molecular weight. Cysteine residues of gliadins mainly form intramolecular disulfide bonds, although α-gliadins with odd numbers of cysteine residues have also been reported. Gliadins are generally regarded to possess globular protein structure, though recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 103 publications
(110 reference statements)
2
65
0
2
Order By: Relevance
“…Uthayakumaran et al (2002) reported that HMW-GS pair 5 þ 10 makes a bigger contribution to dough properties when compared to HMW-GS pair 17 þ 18 and HMW-GS 1 makes the smallest contribution. Previous studies have suggested that gliadins may play an important role in determining the functional property of wheat flour (Barak, Mudgil, & Khatkar, 2012). The influence of gliadins on the bread quality has been debatable for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Uthayakumaran et al (2002) reported that HMW-GS pair 5 þ 10 makes a bigger contribution to dough properties when compared to HMW-GS pair 17 þ 18 and HMW-GS 1 makes the smallest contribution. Previous studies have suggested that gliadins may play an important role in determining the functional property of wheat flour (Barak, Mudgil, & Khatkar, 2012). The influence of gliadins on the bread quality has been debatable for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is the most important cereal crop in the world due to its widespread cultivation and extensive utilization for baked products [1]. The unusual properties of the wheat are ascribed to the presence of gluten forming storage proteins of the endosperm which are further composed of two fractions -the alcohol soluble gliadins and the alcohol insoluble glutenins [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Wheat protein (WP) is one of the most promising polymer materials, and is relatively abundant in various amino acids (eg, glycine, serine, and proline) that are similar to those in collagen proteins in natural bone. [14][15][16] Kim and Kim 17 used WP for surface modification to increase the hydrophilicity of the polymer. Owing to its abundant nutrients and chemical properties, WP is a good candidate material for use in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%